Altered Coupling of Regional Cerebral Blood flow and Brain Temperature in Schizophrenia Compared with Bipolar Disorder and Healthy Subjects. Issue 12 (December 2014) - Ota, Miho; Sato, Noriko; Sakai, Koji; Okazaki, Mitsutoshi; Maikusa, Norihide; Hattori, Kotaro; Hori, Hiroaki; Teraishi, Toshiya; Shimoji, Keigo; Yamada, Kei; Kunugi, Hiroshi
Previous studies have suggested that schizophrenia patients have dysfunctional thermoregulation. The aim of this study was to examine whether brain temperature (BT) in schizophrenia patients differs from that in patients with bipolar disorder and healthy subjects by using magnetic resonance imaging. We also evaluated the possible relationship between BT and cerebral blood flow (CBF). We analyzed the temperature of lateral ventricles as the mean BT using diffusion-weighted imaging (DWI) thermometry, and evaluated the relationships between the BT and the CBF using pseudo-continuous arterial spin labeling (pCASL) among 3 diagnostic groups, 22 male patients with schizophrenia, 19 male patients with bipolar disorder, and 23 healthy male subjects. There were significant positive correlations between BT in the lateral ventricles and CBF in both the patients with bipolar disorder and healthy subjects. By contrast, there were significant negative correlations in patients with schizophrenia. We could not detect the significant difference in the surrogates of BT among three diagnostic groups. We showed that patients with schizophrenia, but not those with bipolar disorder, have dysfunctional thermoregulation in the brain. Brain temperature is highly dependent on cerebral metabolism and CBF, and thus uncoupling of cerebral metabolism and CBF may occur in schizophrenics.